Community Satisfaction With Policing on Guam. (August 2022) - Howes, Loene M.; Watson, Danielle; Ryan, Vanessa; Rivera, John J.; McNinch-Su, Ronald L.
Guam is a Pacific Island in Micronesia with a complex colonial history. Strategically located, Guam is an unincorporated territory of the United States and critical military asset. Policing on Guam is influenced by external stakeholders and budgetary limitations. Recently, a community policing model was introduced to better meet community needs and expectations. This study explored the relevance of predictors of satisfaction with police service provision in the Guamanian context. Residents of Guam ( n = 701) participated in a survey that included demographic characteristics, community context, and police–citizen interactions. Satisfaction with police service provision was predicted by age and perceptions of procedural justice, police performance, and police legitimacy. Higher income predicted lower satisfaction. The findings highlight the importance of police legitimacy and related constructs for satisfaction with police service provision on Guam. Initiatives that focus on police performance and procedural justice may help improve satisfaction with police service provision on Guam.